Tradisi Reba dan Konservasi Uwi (Dioscorea esculenta): Kajian Etnobotani Masyarakat Adat Desa Binawali Kabupaten Ngada - Wae, Veronika P. Sinta Mbia; Nena, Anastasia Modesta; Oka, Elisabet; Surideo, Genoveva Angela (Biocaster : Jurnal Kajian Biologi, 2025)
This study focuses on the Reba tradition and the conservation of yam (Dioscorea esculenta) in Binawali Village, Ngada Regency, through an ethnobotanical approach. The Reba tradition is an annual harvest ritual in which the Ngada ethnic community honors yam as a symbol of life, prosperity, and ancestral heritage. Yam is considered the "bread of life" and their main staple food long before rice and corn were known. Despite having high historical and spiritual value and being easy to cultivate, the utilization of yam is still low, due to the lack of interest of the younger generation and the suboptimal economic utilization which threatens its sustainability as a local agrobiodiversity. This study aims to describe the symbolic meaning of yam in the Reba tradition and examine how the tradition contributes to local and sustainable yam conservation. This study uses a qualitative method with an ethnographic approach, through participant observation, interviews, and documentation of traditional elders, village heads, farmers, and community members for data collection. The results show that the Reba tradition not only functions as an expression of spiritual culture, but also as a mechanism for in situ conservation of yam through customary regulations, management of inherited land, and transmission of local knowledge between generations. This finding emphasizes the importance of strengthening customary institutions as a pillar in community-based agrobiodiversity conservation.